Robust Nanofiber Mats Exfoliated From Tussah Silk for Potential Biomedical Applications - Chen, Ming; Qin, Jianzhong; Lu, Shijun; Zhang, Feng; Zuo, Baoqi (Frontiers in Bioengineering and Biotechnology, 2021)
Nanofiber as elements for bioscaffolds are pushing the development of tissue engineering. In this study, tussah silk was mechanically disintegrated into nanofiber dispersed in aqueous solution which was cast to generate tussah silk fibroin (TSF) nanofiber mats. The effect of treatment time on the morphology, structure and mechanical properties of nanofiber mats were examined. SEM indicated diameter decreasing of nanofiber with shearing time, and the diameter of nanofiber was 139.7 nm after 30 min treatment. These nanofiber mats exhibited excellent mechanical properties, the breaking strength increased from 26.31MPa to 72.68 MPa with the decrease of fiber diameter from 196.5 to 139.7 nm. The particulate debris was observed on protease XIV degraded nanofiber mats, and greater than 10% weight loss after 30 days in vitro degradation. Cell compatibility experiment confirmed adhesion and spreading of NIH-3T3 cells, and enhanced cell proliferation on TSF nanofiber mats compared to Bombyx mori silk nanofiber mats. In conclusion, results indicate that TSF nanofiber mats prepared here is mechanical robust, slow biodegradable, and biocompatible material, and has promising application in regenerative medicine.